Analisis Pengaruh Risk Profile, Good Corporate Governance, Earning, Capital terhadap Tingkat Kepercayaan Masyarakat dengan Kinerja Perbankan Syariah Sebagai Variabel Intervening (Studi Kasus Bank Umum Syariah - Ritonga, Sahdini Arofah (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This study aims to determine the level of banking soundness to increase public trust in Islamic Commercial Banks in Indonesia, to find out what obstacles are felt by the public in the services provided by the Bank. This study uses a quantitative approach method. The data collection technique and instrument used was purposive sampling. During the observation period it shows that the research data contained in the Risk Profile has a positive effect on public trust. This shows that the higher the Risk Profile, the higher the public's trust. In GCG there is a positive influence on public trust. This shows that the higher the GCG, the more it will affect public trust. There is a positive and significant effect of Earning on public trust. This shows that the higher the Earning, the higher the public's trust. In the Capital Variable there is a positive and significant influence on public trust. This shows that the higher the Capital, the higher the public's trust.